2020
DOI: 10.1038/s41598-020-71706-3
|View full text |Cite
|
Sign up to set email alerts
|

Ivabradine is as effective as metoprolol in the prevention of ventricular arrhythmias in acute non-reperfused myocardial infarction in the rat

Abstract: Ventricular arrhythmias are a major source of early mortality in acute myocardial infarction (MI) and remain a major therapeutic challenge. Thus we investigated effects of ivabradine, a presumably specific bradycardic agent versus metoprolol, a β-blocker, at doses offering the same heart rate (HR) reduction, on ventricular arrhythmias in the acute non-reperfused MI in the rat. Immediately after MI induction a single dose of ivabradine/ metoprolol was given. ECG was continuously recorded and ventricular arrhyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Pacing to maintain unchanged HR essentially abolished protective effects of ivabradine, suggesting that HR reduction is the principal mechanism of its antiarrhythmic action [ 64 ]. Other experimental studies support this conclusion: we showed that ivabradine and metoprolol provided similar protection against VA induced by acute non-reperfused MI when given at doses that ensured identical HR reduction [ 57 ]. Similarly, ivabradine increased time to onset of ischemia-related conduction slowing and loss of electrical excitability and protected against development of VF during reperfusion in a model of 8-minute ischemia and reperfusion in an isolated rat heart [ 60 ].…”
Section: Ivabradine and Ventricular Arrhythmiassupporting
confidence: 55%
See 3 more Smart Citations
“…Pacing to maintain unchanged HR essentially abolished protective effects of ivabradine, suggesting that HR reduction is the principal mechanism of its antiarrhythmic action [ 64 ]. Other experimental studies support this conclusion: we showed that ivabradine and metoprolol provided similar protection against VA induced by acute non-reperfused MI when given at doses that ensured identical HR reduction [ 57 ]. Similarly, ivabradine increased time to onset of ischemia-related conduction slowing and loss of electrical excitability and protected against development of VF during reperfusion in a model of 8-minute ischemia and reperfusion in an isolated rat heart [ 60 ].…”
Section: Ivabradine and Ventricular Arrhythmiassupporting
confidence: 55%
“…Preclinical studies of ivabradine are summarized in Table 1 . Briefly, ivabradine reduced ventricular arrhythmias (VA, both ventricular tachycardia [VT]/ventricular fibrillation [VF] and premature ventricular complexes [PVC]), arrhythmic deaths and total mortality in the rat model of non-reperfused acute MI, both when given as prophylaxis [ 25 ] and within the first minutes of ischemia [ 57 ] and was as effective as metoprolol in the latter study. Furthermore ivabradine increased VF threshold during acute myocardial ischemia in the pig [ 58 , 59 ], reduced VA during ischemia and reperfusion in the isolated rat heart [ 60 ].…”
Section: Ivabradine and Ventricular Arrhythmiasmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been revealed that Iva slows heart rate by reducing the slope of the diastolic depolarization of pacemaker action potential, without affecting cardiac inotropy or systemic vascular resistance [ 10 ]. Emerging evidence has proven the efficacy and safety of Iva in other cardiovascular diseases such as inappropriate sinus tachycardia [ 11 ] and ventricular arrhythmias [ 12 ]. However, the guidelines of Iva in the application of acute coronary syndromes has not been established.…”
Section: Introductionmentioning
confidence: 99%